VALUING ATHLETES - Gusenzow, Chris; Tower, Greg (The journal of contemporary issues in business and government, 2006)
How does a sports team determine the value of its athletes? How should such information be communicated? Is silence misleading? In this study measurement models are explored to advance suggestions for improvement for reporting. Data from a large scale survey reveals that 62 percent of Australian Football League (AFL)- linked personnel disagreed with the idea of valuing players on their team's balance sheet. Statistical analysis identifies three clearly different categories; club/AFL management, player management (players, agents and players' union) and accountants/accounting academics. Each groups' views are significantly different with less, some and majority support for athlete valuation respectively. However, there may be a rising need to value such company assets. AFL clubs are being battered by increased transparency expectations of better and clearer communication. It is argued that the provision of providing player valuation information from a 'public interest' viewpoint would be beneficial for the hundreds of thousands of club members.